2000
DOI: 10.1292/jvms.62.281
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of the Role of Antigenic Keratan Sulphate Reacting to a 1/14/16H9 Antibody as a Molecular Marker to Monitor Cartilage Metabolism in Horses

Abstract: ABSTRACT. The role of keratan sulphate (KS) as a marker of cartilage metabolism was evaluated by using an in vitro model of equine articular cartilage. Articular cartilage was harvested from clinically healthy 6-month-old foals (n=3). Chondrocytes were centrifuged and cultured as pellets. Chondrocyte pellets were stimulated by insulin-like growth factor (IGF)-Iα or interleukin (IL)-1α for 2 weeks. The sulfated glycosaminoglycans (GAG) and antigenic KS concentrations in the culture media were measured by a 1,9-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…1). An in vitro study suggested that 1/14/16H9 antibody-reactive KS in serum and synovial fluid could contribute to the understanding of the catabolic process of articular cartilage metabolism (Okumura et al, 2000). Serum KS concentration in animals younger than 2 months of age has been found to be significantly higher than the levels in older dogs and horses (Leipold et al, 1989;Okumura et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). An in vitro study suggested that 1/14/16H9 antibody-reactive KS in serum and synovial fluid could contribute to the understanding of the catabolic process of articular cartilage metabolism (Okumura et al, 2000). Serum KS concentration in animals younger than 2 months of age has been found to be significantly higher than the levels in older dogs and horses (Leipold et al, 1989;Okumura et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, an inhibition enzyme‐linked immunosorbent assay (ELISA) using a sensitive anti‐equine KS antibody 1/14/16H9 has led to improvements in the measurement of low concentrations of KS in horses (Okumura and Fujinaga, 1998). An in vitro study has suggested that 1/14/16H9 antibody‐reactive KS in serum and synovial fluid could be used as a non‐invasive cartilage metabolic marker to assist in understanding the catabolic process of articular cartilage metabolism (Okumura et al., 2000).…”
Section: Introductionmentioning
confidence: 99%